High Prevalence of Multiple Arterial Bed Lesions in Patients With Fibromuscular Dysplasia: The ARCADIA Registry (Assessment of Renal and Cervical Artery Dysplasia). Issue 3 (September 2017) - Plouin, Pierre-François; Baguet, Jean-Philippe; Thony, Frédéric; Ormezzano, Olivier; Azarine, Arshid; Silhol, François; Oppenheim, Catherine; Bouhanick, Béatrice; Boyer, Louis; Persu, Alexandre; Hammer, Frank; Gosse, Philippe; et al.
Abstract : Fibromuscular dysplasia (FMD) commonly affects the renal and cervical arteries but has been described to affect other vascular beds as well. The prevalence of and clinical characteristics associated with multisite FMD (string-of-beds or focal stenoses affecting at least 2 vascular beds) are not known. In the prospective ARCADIA registry (Assessment of Renal and Cervical Artery Dysplasia), symptomatic patients with renal artery (RA) FMD underwent tomographic- or magnetic resonance-angiography from the aortic arch to the intracranial arteries and those with cervical FMD from the diaphragm to the pelvis. Of 469 patients (84.0% women), 225 (48.0%) had multisite FMD. In addition, 86 of 244 patients with single-site disease had dissections or aneurisms affecting other vascular beds, totaling 311 patients (66.3%) with lesions in >1 vascular bed. Among patients with a cerebrovascular presentation, the prevalence of RA lesions was higher in patients with than in those without hypertension (odds ratio, 3.4; 95% confidence interval, 1.99–6.15). Among patients with a renal presentation, the prevalence of cervical lesions was higher in patients with bilateral than in those with unilateral RA lesions (odds ratio, 1.9; 95% confidence interval, 0.99–3.57). In conclusion, FMD is a systemic arterial disease. At least 2 vascular beds were affected by dysplastic stenoses in 48.0% of cases and by dysplastic stenoses, aneurysms, and dissections in 66.1% of cases. RA imaging should be proposed to hypertensive patients with a cerebrovascular presentation. Cervical artery imaging should be considered in patients with a renal presentation and bilateral RA lesions. Clinical Trial Registration—: URL:www.Clinicaltrials.gov . Unique identifier: NCT02884141. Abstract : Supplemental Digital Content is available in the text.